Usulan Model Sistem Antrian Pengisian Bahan Bakar di Salah Satu SPBU di Kota Cilegon Menggunakan Simulasi Diskrit - Nabhansyah, Muhammad; Hidayat, Rahmat; Risvanto, Ridho Happy; Maulana, Rifan Nur; Shofa, Mohamad Jihan (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This study analyzes the queuing system for motorcycle fuel filling at a gas station in Cilegon city using discrete simulation. The gas station often faces long queues that cause inconvenience and decrease operational efficiency. The research method includes collecting primary data through direct observation to obtain information on the number of vehicle arrivals, service time, and the number of operating booths. Secondary data is obtained from the literature related to queuing systems. After the data is collected, distribution analysis is conducted to understand the arrival and service patterns. A simulation model is created and tested using Arena Software. Model verification and validation ensure the accuracy of the simulation results. The research findings show that in the initial model, 54 vehicles were served in 50 minutes with an average waiting time of 45.9506 seconds. The first improvement scenario added one operator to each server, while the second scenario added a new server with two operators. The second scenario provided the best results with 106 vehicles served in 50 minutes and the waiting time reduced to 31.6773 seconds, showing a significant increase in system efficiency. The percentage increase in the number of vehicles served is approximately 96.30%, while the waiting time decreased by 31.06%. The implementation of the second scenario is expected to reduce queues and improve customer satisfaction and operational efficiency at the gas station. Keywords: Arena, Gas Station, Queue, Simulation